Pebble accretion onto planets in turbulent discs. Issue Volume 14:Issue S345(2019) (August 2018) - Kley, Wilhelm; Picogna, Giovanni; Stoll, Moritz H. R.
Abstract: Planets form in protoplanetary accretion discs around young protostars. These discs are driven by internal turbulence and the gas flow is not laminar but has stochastic components. For weakly ionised discs the turbulence can be generated purely hydrodynamically through the vertical shear instability (VSI). Embedded particles (dust/pebbles) experience a hydrodynamic drag and drift inward radially and are stirred up vertically by the turbulent motion of the disc. We study the accretion of particles onto a forming planet embedded in a VSI turbulent protoplanetary disc through a series of 3D hydrodynamical simulations for locally isothermal discs with embedded planets in the mass range from 5 to 100 Earth masses ( M 2295 ).